Paralympic sports, the next frontier for sports science - Keogh, J. W. L. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
The Paralympic Games is the pinnacle of sport for many athletes with a disability. The purpose of this paper is to briefly provide some background on the Summer Paralympic Games and their eligibility and classification rules. Results from selected studies examining the biomechanics of locomotion (amputee running, swimming and wheelchair pushing) and projecting external objects (e.g. throwing and hitting) as well as the evolution of sports performance and training practices such as strength and conditioning will be described. Recommendations for how this evidence can be used to improve athletic performance in Paralympic sports and inform future research are also provided.